Campaigns and elections American style - Thurber, James A. \ Nelson, Candice J. (San Francisco : Westview Press, 1995)
The transformation of american campaigns, 1. -- The principles of planning, 14. -- Who will vote for you and why : Designing strategy and theme, 30. -- Contemporary strategy and agenda setting, 47. -- Strategy and tactics for campaign fundraising, 62. -- Competition, contributions, and money in 1992, 78. -- Paid media advertising, 84. -- Winning through advertising : It's all in the context, 101. -- The best campaign wins : Local press ceverage of nonpresidential races, 112. -- Reporting campaigns : Reforming the press, 126. -- Organizing the field, 138. -- Field work, political parties and volunteerism, 152. -- Political polling : From the beginning to the center, 161. -- The promising adolescence of campaign surveys, 181. -- The ethics of political campaigns, 192. -- Campaing ethics and political trust, 200. -- Strategic perspectives on the 1992 campaign, 213. -- Do campaigns matter?, 224